Cefdinir and β-Lactamase Inhibitor Independent Efficacy Against Mycobacterium tuberculosis - Srivastava, Shashikant; Thomas, Tania; Howe, Dave; Malinga, Lesibana; Raj, Prithvi; Alffenaar, Jan-Willem; Gumbo, Tawanda (Frontiers in Pharmacology, 2021)
Background. There is renewed interest in repurposing beta-lactam antibiotics for treatment of tuberculosis (TB). We investigated efficacy of cefdinir, that withstand the -lactamase enzyme present in many bacteria, against drug-susceptible and multi-drug resistant (MDR) Mycobacterium tuberculosis (Mtb). Methods. Minimum inhibitory concentration (MIC) experiments were performed with Mtb H37Ra, eight drug-susceptible, and 12 MDR-TB clinical isolates with and without the beta-lactamase inhibitor, avibactam at 15 mg/L final concentration. Next, we performed dose-response study with Mtb H37Ra in test-tubes followed by a sterilizing activity study in the pre-clinical hollow fiber model of tuberculosis (HFS-TB) study using an MDR-TB clinical strain. Inhibitory sigmoid Emax model was used to describe the relationship between the drug exposure and bacterial burden. Results. Cefdinir MIC for Mtb H37Ra was 4 mg/L and 2 mg/L with or without avibactam, respectively. The MIC of the clinical strains ranged between 0.5 to 16 mg/L. In the test-tube experiments, cefdinir killed 4.93+0.07 log10 CFU/mL Mtb H37Ra in 7-days. In the HFS-TB studies, cefdinir showed dose-dependent killing of MDR-TB, without combination of avibactam. The cefdinir PK/PD index linked to the Mtb sterilizing efficacy was identified as the ratio of area under the concentration-time curve to MIC (AUC0-24/MIC) and optimal exposure was calculated as AUC0-24/MIC 578.86. There was no resistance emergence to cefdinir in the HFS-TB. Conclusion. In the HFS-TB model, cefdinir showed efficacy against both drug susceptible and MDR-TB without combination of -lactamase inhibitor. However, clinical validation of these findings remains to be determined.